Self-reported health-related experiences, psychological capital, and psychological wellbeing in Lithuanian adults sample - Diržytė, Aistė (Health Psychol Open, 2021)
The purpose of this research was to examine psychological wellbeing and psychological capital in groups of subjectively healthy and unhealthy individuals and identify significant associations. We have analyzed the results of a Lithuanian representative sample of adults (n = 1001). Results showed that adult respondents who reported the absence of cardiovascular diseases, nervous system diseases, autoimmune diseases, diabetes, vision disorders, physical or mental disability, and substance abuse demonstrated significantly higher scores for flourishing, life satisfaction, psychological capital, self-efficacy, hope, and resilience. The model on associations between the number of reported diseases, psychological capital, and wellbeing in the representative sample of adults (χ(2) = 110.786, df = 16; CFI = .981; RMSEA = .077; NFI = 0.978; TLI = 0.968) indicated that a higher number of diseases (per person) predicts a weakening effect on psychological capital, while psychological capital predicts psychological wellbeing.